Prolonged exposure therapy for PTSD : emotional processing of traumatic experiences : therapist guide - Foa, Edna B.; Hembree, Elizabeth Ann; Rothbaum, Barbara Olasov; Rauch, Sheila A. M. (New York : Oxford University Press, 2019)
'The second edition ... provides all of the tools necessary for trained mental health providers to implement this first-line PTSD treatment with their patients. This model is individualized to address the needs of a variety of trauma survivors. Leaders in clinical practice, training, and research in the field of PTSD treatment, the authors have revised the Guide throughout to reflect the many advances in PTSD research that have occurred since the release of the first edition, including key adjustments to the underlying theory as well as additional evidence for modifications and individualization for more complex patient presentations and military populations. The Guide provides a concise but thorough description of the key components of the program, how to implement them, and when and how to consider adaptations."--Provided by publisher.
Foundations of prolonged exposure -- Assessing trauma survivors and implementing PE in practice -- Session 1 -- Session 2 -- Session 3 -- Intermediate sessions -- Final session -- Tailoring treatment to the individual : promoting effective engagement.
Includes bibliographical references.
Keywords: Post-traumatic stress disorder -- Treatment; Cognitive therapy